2020
DOI: 10.31585/jbba-3-1-(6)2020
|View full text |Cite
|
Sign up to set email alerts
|

Emerging regulatory approaches to blockchain based token economy

Abstract: Blockchain-enabled digital scarcity has opened up a whole new dimension of possibilities for the token economy, particularly with regard to rights and assets that have not been traded electronically before. Blockchain-based tokenization of rights and assets has also brought a new set of legal and regulatory challenges. Regulators and legislators are yet to address many of the issues raised by blockchain-based tokenization, from decentralisation and token characterisation to cross-border harmonisation and regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Overall, our analysis of 10-K reports suggests that most public corporations are moving more slowly to the token economy than suggested by media coverage or do not yet recognise the impact the token economy will have on their business. The nascent and evolving legislative and regulatory infrastructure around the token economy complicates adoption of these technologies and recognition of material impacts [6]. This makes us ask: Will incumbents be ready for the disruption caused by the token economy?…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our analysis of 10-K reports suggests that most public corporations are moving more slowly to the token economy than suggested by media coverage or do not yet recognise the impact the token economy will have on their business. The nascent and evolving legislative and regulatory infrastructure around the token economy complicates adoption of these technologies and recognition of material impacts [6]. This makes us ask: Will incumbents be ready for the disruption caused by the token economy?…”
Section: Discussionmentioning
confidence: 99%
“…Regulators have identified that the illegal use of blockchain based virtual currencies includes money laundering and terror financing [9]. There have been studies conducted for establishing emerging regulatory approaches for the future of blockchain based token economies [21]. None of the existing blockchain protocols, be them permissionless or permissioned, are designed with regulation in the consensus mechanism itself [26,28,29].…”
Section: Susceptibility Of Existing Blockchains Towards Illegal Trans...mentioning
confidence: 99%
“…This further complicates efforts to generalise acceptable levels of privacy threat across different users and contexts. Fourth, designing regulation is challenging when technologies are still maturing, as the nature and scale of risks are typically unclear, and governments do not want to act prematurely and impede innovation (Ferreira, 2020; Hamburg, 2012; Kiviat, 2015; Roca et al, 2017). This reticence by governments could open the door for other regulators, but it is not clear which other entities, if any, have the right or means to impose regulation.…”
Section: Privacy and The Regulation Of Emerging Technologiesmentioning
confidence: 99%
“…Meanwhile, regulators see the lack of control around blockchain as a potential blind spot for criminal activity such as money laundering and terrorist financing (cf. Amarasinghe et al, 2019; Bordo and Levin 2017; De Filippi, 2014; Elias, 2011; European Banking Association (EBA), 2019; Ferreira, 2020; Foley et al, 2019; Genkin et al, 2018; Goodell and Aste, 2019; Gruber, 2013; Juels et al, 2016; Miller et al, 2017; Molloy, 2018; Möser et al, 2013; Rueckert, 2019; Weber et al, 2019; Zyskind et al, 2015).…”
Section: Introductionmentioning
confidence: 99%